2019
DOI: 10.4103/ijstd.ijstd_67_17
|View full text |Cite
|
Sign up to set email alerts
|

A study on hypogonadism in male HIV patients in northeastern part of India

Abstract: Context: After the introduction of highly active antiretroviral therapy (ART), the prevalence of hypogonadism among human immunodeficiency virus (HIV)-infected males is decreasing. Aims: The aim of this study was (i) to estimate the prevalence of hypogonadism among HIV-infected males and (ii) to determine the risk factors for hypogonadism. Settings and Design: This was a cross-sectional study undertaken at ART center of a medical Institute. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…Rochira et al [ 4 ] reported secondary hypogonadism in 86 percent of hypogonadal patients with testosterone <300 ng/dl. Similarly, in the study by Pongener et al [ 31 ] and Dutta et al [ 32 ], hypogonadotropic hypogonadism was found in 86% and 81% of hypogonadal patients, respectively. This observation could be due to invasion of the hypothalamic pituitary axis by the virus leading to impairment of its function.…”
Section: Discussionsupporting
confidence: 56%
“…Rochira et al [ 4 ] reported secondary hypogonadism in 86 percent of hypogonadal patients with testosterone <300 ng/dl. Similarly, in the study by Pongener et al [ 31 ] and Dutta et al [ 32 ], hypogonadotropic hypogonadism was found in 86% and 81% of hypogonadal patients, respectively. This observation could be due to invasion of the hypothalamic pituitary axis by the virus leading to impairment of its function.…”
Section: Discussionsupporting
confidence: 56%
“…The previous studies reported no significant correlation between the duration of ART and gonadal dysfunction [26][27][28]. Similarly, we found a weak negative correlation between ART regimen duration and ED when ST was abnormal (P=0.093).…”
Section: Acknowledgmentsupporting
confidence: 60%
“…Hypogonadism is a relatively common finding in men with HIV, although its prevalence is at present lower comparing to the preantiretroviral therapy (ART) era [4,5]. Current estimates on the prevalence of hypogonadism in HIV-infected men generally range from 13 to 40% according to different study settings, mainly depending on the criteria and T-levels cut-offs used for its diagnosis [6,7]. Importantly, hypogonadism in HIV-infected men might result from either testicular disorder (primary hypogonadism) or hypothalamic-pituitary dysfunction (secondary hypogonadism); however, only few studies differentiated between these two forms by testing luteinizing hormone (LH) levels, which are elevated in the former case and low/normal in the latter.…”
Section: Introductionmentioning
confidence: 99%